2014
DOI: 10.1007/s12210-014-0312-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of drainage systems and intermontane basins in the Quaternary landscape of the Central Apennines chain (Italy)

Abstract: The Central Apennines chain (Central Italy) is an asymmetric NW-SE thrust belt, NE verging, that has developed since the Neogene. The present landscape is made up of alternating calcareous ridges, valleys on pelitic arenaceous bedrock, as well as wide intermontane basins filled by Quaternary continental deposits. The chain is characterised at high elevation by glacial and isolated patches of dissected karst relict landscapes elevations, and by slope landforms, alluvial fans and fluvial landforms within valleys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…While lakes were widespread during the Early-Middle Pleistocene in this area, most of them disappeared in the course of the Middle-Late Pleistocene as tectonic basins became progressively fluvially connected (e.g. D' Agostino et al, 2001;Piacentini & Miccadei, 2014). Understanding the mechanisms that control drainage integration is clearly important for interpreting the stratigraphic record preserved in such extensional settings.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…While lakes were widespread during the Early-Middle Pleistocene in this area, most of them disappeared in the course of the Middle-Late Pleistocene as tectonic basins became progressively fluvially connected (e.g. D' Agostino et al, 2001;Piacentini & Miccadei, 2014). Understanding the mechanisms that control drainage integration is clearly important for interpreting the stratigraphic record preserved in such extensional settings.…”
Section: Introductionmentioning
confidence: 94%
“…Based mainly on these sediments, it has been concluded that many large lakes coexisted during the Lower-Middle Pleistocene suggesting that endorheic drainage was prevalent at that time (D'Agostino et al, 2001;Piacentini & Miccadei, 2014). In other words, a temporal transition is inferred to have occurred from internal to external drainage leading to the integration of previous isolated basins with the regional river network (Bartolini et al, 2003;D'Agostino et al, 2001;Piacentini & Miccadei, 2014). In other words, a temporal transition is inferred to have occurred from internal to external drainage leading to the integration of previous isolated basins with the regional river network (Bartolini et al, 2003;D'Agostino et al, 2001;Piacentini & Miccadei, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Ma, probably due to slab detachment under the central Apennines (Faccenna et al, 2014). The second phase of mantle upwelling could be responsible for the strong tectonic uplift (~260 m) that occurred in central Italy close to the Gelasian-Calabrian transition (Cosentino et al, 2009), which possibly induced the early Pleistocene reorganization of the central Apennine drainage systems (Fubelli et al, 2014;Piacentini and Miccadei, 2014).…”
Section: New Insights Into the Evolution Of The Apennine Postorogenicmentioning
confidence: 99%
“…The fluvial deposits are arranged in at least four orders of terraces, while the slope deposits belong to two different generations. Their age ranges from the Lower-Middle Pleistocene to the Holocene (Capelli, Miccadei, & Raffi, 1997;Piacentini & Miccade, 2014).…”
Section: Study Area: Castel DI Sangro Plainmentioning
confidence: 99%